Society, history, and the global human condition : essays in honor of Irving M. Zeitlin - Baber, Zaheer; Bryant, Joseph M., 1954-; Zeitlin, Irving M. (Lexington Books, 2010)
This Festschrift for Irving M. Zeitlin honors a scholar whose work has influenced and continues to influence sociology, particularly classical sociological theory, sociology of religion, and historical sociology. Irving M. Zeitlin's scholarship andmentoring has also influenced and inspired a new generation of sociologists. The essays presented here address a wide range of topics that include classical sociological theory, globalization, bureaucracy, genocide, resistance, ethnic diversity, the intifada, anti-Semitism, democracy, geopolitical theory, war literature, science, and national culture.